Roads to Smart Artificial Microswimmers - Alan C. H. Tsang; Ebru Demir; Yang Ding; On Shun Pak (Advanced Intelligent Systems, 2020)
Artificial microswimmers offer exciting opportunities for biomedical applications. The goal of these synthetics is to swim like natural micro‐organisms through biological environments and perform complex tasks such as drug delivery and microsurgery. Extensive efforts in the past several decades have focused on generating propulsion at the microscopic scale, which has engendered a variety of artificial microswimmers based on different physical and physicochemical mechanisms. Yet, these major advancements represent only the initial steps toward successful biomedical applications of microswimmers in realistic scenarios. A next step is to design “smart” microswimmers that can adapt their locomotion behaviors in response to environmental factors. Herein, recent progress in the development of microswimmers with intelligent behaviors is surveyed in three major areas: 1) adaptive locomotion across different media, 2) tactic behaviors in response to environment stimuli, and 3) multifunctional swimmers that can perform complex tasks. The emerging technologies and novel approaches used in developing these “smart” microswimmers, which enable them to display behaviors similar to biological cells, are discussed.